HOW TO USE DIGITAL LITERACY AS A LEARNING RESOURCE FOR TEACHER CANDIDATES IN INDONESIA - Evi Fatimatur Rusydiyah; Eni Purwati; Ardhi Prabowo (Jurnal Cakrawala Pendidikan, 2020)
In the current era, the world of education faces challenges of how to design learning by using digital media with the intention to improve the instructional quality and students’ competencies. Digital media are important in the world of education since they are able to present materials contextually, visually, interestingly, and interactively. The present study was aimed at identifying teacher-candidate students’ perceptions on the use of digital literacy as a learning resource. The study was a survey involving students of the universities that had a partnership with USAID Priority as the research population. A sample of 168 students was selected from seven such universities. Data were collected using questionnaires, interviews, and documentation. The weighting of the questionnaire scores used the Likert’s scale. The variable Digital Literacy consisted of four indicators of ICT basic competencies, informational skills, media awareness, and computational thinking. Findings show that the teacher-candidate students have good perceptions in the use of digital literacy as a learning resource. On the ICT basic skill indicator, the average score is at the high category; on the informational skill indicator, the average score is at the very high category; on the media awareness, the average score is at the high category; and on the computational thinking indicator, the average score is at the medium category.